Examen
Examen
Examen
2 ∙ y2 + 8 ∙ x − 4 ∙ y + x2 − 4 = y2 − 8 + 4 ∙ y
solución:
agrupando términos, resulta:
2 ∙ y 2 + 8 ∙ x − 4 ∙ y + x 2 − y 2 − 4 ∙ y = −8 + 4 → x 2 + 8 ∙ x + y 2 − 8 ∙ y = −4
solución:
evaluando, resulta:
1 1
3∙cos( ∙π∙x) 3∙cos( ∙π∙1)
lím ln (cos(2 ∙ π) ∙ (x ∙ z) + e 2 ) = ln (cos(2 ∙ π) ∙ (1 ∙ 1) + e 2 ) = ln(1 + 1) = ln(2)
(x,y,z)→(1,1,1)
solución:
2
fx (x, y) = λ ∙ g x (x, y) → (4) = λ ∙ (2 ∙ x) → λ =
x
3
fy (x, y) = λ ∙ g y (x, y) → (6) = λ ∙ (2 ∙ y) → λ =
y
por lo tanto:
3
y = ∙ (±2) = ±3
2
solución:
escribamos la función como f(x, y) = e3∙x ∙ e5∙y
se tiene que:
∂f(x, y)
= (e3∙x )′ ∙ e5∙y + e3∙x ∙ (e5∙y )′ = 0 ∙ e5∙y + e3∙x ∙ e5∙y ∙ (5) = 5 ∙ e3∙x ∙ e5∙y
∂y
luego:
∂2 f(x, y)
= 5 ∙ ((e3∙x )′ ∙ e5∙y + e3∙x ∙ (e5∙y )′ ) = 5 ∙ (e3∙x ∙ (3) ∙ e5∙y + e3∙x ∙ 0) = 15 ∙ e3∙x ∙ e5∙y
∂x ∂y
finalmente:
∂3 f(x, y)
= 15 ∙ ((e3∙x )′ ∙ e5∙y + e3∙x ∙ (e5∙y )′ ) = 15 ∙ (e3∙x ∙ (3) ∙ e5∙y + e3∙x ∙ 0) = 45 ∙ e3∙x ∙ e5∙y = 45 ∙ e3∙x+5∙y
∂x 2 ∂y